KAJIAN DISTRIBUSI RASKIN DI KABUPATEN SUMEDANG - Lies Sulistyowati; Andrian Nur Ramadhan (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2017)
Raskin is one of the Indonesian government programs that have been implemented since 2002, aimed at reducing the burden of expenditure of poor households as a form of support to improve the food security of society. However, in practice often the target of five right is not reached or less effective and efficient. This study aimed to analyze the effectiveness and efficiency of the distribution of Raskin to get to the target beneficiary households (RTS-PM) Raskin. Jatinangor District and BuahduaDistrict. The design study is quantitative descriptive survey techniques. Sampling techniques Two--stage random cluster sampling, with 82 recipients Raskin. The results of the study concluded that overall assessment of the effectiveness of RTS-PM Raskin distribution is effective (a weighted average of 2.94). While per indicator: in terms of targeting accuracy of 2.29 (not exact), the accuracy of the amount of 1.96 (not exact), the accuracy of the price 3.65 (right), timeliness of 3.80 (right) and accuracy of quality 3.05 (quite rightly). Raskin distribution efficiency level of 0.025, then the distribution of Raskin in Sumedang can be said to be efficient. If compared beetwen JatinangorDistrict and Buahdua District, then the implementation of Raskin in District Jatinangor more effectively and efficiently than in the District Buahdua.